Thyroxine replacement promptly corrects vaginal bleeding in precocious menarche due to Van Wyk Grumbach syndrome - Amin, Sapna Vinit; Bharatnur, Sunanda; Vasudeva, Akhila; Hebbar, Shripad S. (International Journal of Contemporary Pediatrics, 2017)
Van Wyk Grumbach syndrome is a rare complication of a common endocrine disorder, i.e., hypothyroidism, but occurs when it is long standing during periods of pre-pubertal growth. It can occur in both sexes, in boys it is associated with testicular enlargement and in girls, the usual presenting features are early onset menarche, enlarged bilateral multicystic ovaries and delayed skeletal growth. Diagnosing this condition is very important as unnecessary surgical intervention for ovarian enlargement is avoided. Prompt replacement therapy with thyroxine not only corrects menstrual abnormality, but also ovaries return to normal over period of time. In this case report, we describe an unusual case of irregular vaginal bleeding, large multicystic ovaries and delayed bone age in a young girl due to autoimmune thyroiditis who promptly responded to levo-thyroxine.